Diagnosis of a defect in the uterine wall using 3D ultrasound in the 16th week of gestation - López Ramón y Cajal, Carlos; Rodríguez Fernández, Vanesa (Clinical case reports, 2017)
Key Clinical Message The 3D volumetric transabdominal study with rendering mode is a very useful tool to perform a detailed study of the uterine wall, and it allows us to create a safe and early strategy during pregnancy in uterine dehiscences, as we show in this case in the 16th week of gestation. The 3D volumetric transabdominal study with rendering mode is a very useful tool to perform a detailed study of the uterine wall, and it allows us to create a safe and early strategy during pregnancy in uterine dehiscences, as we show in this case in the 16th week of gestation.